Bioactive halogenated dihydroisocoumarins produced by the endophytic fungus Lachnum palmae isolated from Przewalskia tangutica. (April 2018) - Zhao, Min; Yuan, Lv-Yi; Guo, Da-Le; Ye, Ye; Da-Wa, Zhuo-Ma; Wang, Xiao-Ling; Ma, Feng-Wei; Chen, Lei; Gu, Yu-Cheng; Ding, Li-Sheng; Zhou, Yan
Abstract: Guided by the UPLC-ESIMS profile, seven previously undescribed halogenated dihydroisocoumarins, palmaerones A-G, along with eleven known dihydroisocoumarins, were isolated from Lachnum palmae, an endophytic fungus from Przewalskia tangutica by exposure to a histone deacetylase inhibitor SAHA. Structures of the isolates were elucidated by analysis of their NMR, MS and optical rotation values. The antimicrobial, anti-inflammatory and cytotoxic activities of palmaerones A-G were evaluated. Palmaerones A-G showed antimicrobial activities against the strains ( C. neoformans, Penicillium sp., C. albicans, B. subtilis and S. aureus ), and palmaerone E exhibited potential antimicrobial activities against all the test strains with the MIC value in the range of 10–55 μg/mL. Palmaerones A and E exhibited moderate inhibitory effects on NO production in LPS-induced RAW 264.7 cells, with the IC50 values of 26.3 and 38.7 μM, respectively and no obvious toxicities were observed at 50 μM. Palmaerone E showed weak cytotoxicity against HepG2 with the IC50 value of 42.8 μM. This work provides an effective strategy for expanding natural product resource. Graphical abstract: Seven previously undescribed halogenated dihydroisocoumarins were isolated from Lachnum palmae by exposure to SAHA. The antimicrobial, anti-inflammatory and cytotoxic activities of the previously undescribed compounds were evaluated. Highlights: Seven previously undescribed dihydroisocoumarins were isolated from Lachnum palmae. Their structures were elucidated by extensive spectroscopic analysis. Palmaerone E exhibited potential antimicrobial activities against all the test strains. Palmaerones A and E exhibited moderate NO inhibitory activities in RAW 264.7 cells. Palmaerone E showed weak cytotoxicity against HepG2.